Between East and West: Reassessing and Rediscovering Pearl S. Buck - Santander Oliván, Mario (Sinología hispánica. China Studies Review, 2024)
This paper is intended to be a tribute to the figure of Pearl S. Buck (1892-1973) on the occasion of the fiftieth anniversary of her death, reassessing and rediscovering her popularity in the West, her experience in China, and her literary authority worldwide. Pearl S. Buck was one of the most popular and controversial American writers of the 20th century. Her work was crucial in the perceptions of Westerners in general and Americans in particular of China and in promoting a stronger cultural understanding between the West and the East. Pearl S. Buck spent a considerable time in China, which gave her some authority to speak, write, and opine about that country. But what kind of authority? Why have her works been translated to more than a hundred languages and been read by millions of people around the world? Why does she still remain one of the least studied writers in the Western literary history? From what point of view should her writing be analysed? Is she still a popular author in the 21st century? This paper attempts to answer these and other questions related to the figure of Pearl S. Buck and is intended as an invitation to discuss a topic that needs further research in the field of East Asian Studies.